On the Role of Goal Dysregulation in the Treatment of Bipolar Disorder. - Miklowitz, D; Johnson, S (2009)
Nusslock, Abramson, Harmon-Jones, Alloy, and Coan (this issue) propose that current psychosocial treatments for bipolar disorder be supplemented with interventions focused on altering goal dysregulation pathways. While innovations to existing treatment manuals are always welcome, there are several reasons why this suggestion may require further consideration. We highlight issues pertaining to the status of cognitive-behavioral therapy for bipolar disorder, the distinction between education and psychoeducation, the nature of familial expressed emotion, differences between clinical and analog samples, and the larger question of how to assess mechanisms in psychosocial treatment studies. We also raise the question of whether an optimistic goal orientation can be a protective factor in patients' long-term coping with bipolar disorder.